Design of switchable filtenna using spdt switch for wireless communications - Abdullah Nasser, Zayed Abdo (2022)
The radio frequency front ends system consists of many functional blocks, such as antenna filters, power amplifiers (PAs), switches, and many more. Conventionally, they are cascaded in wireless systems, which suffer from large size, high loss, or efficiency degradation due to impedance mismatching. One of the measures taken to improve the RF front end is by integrating the filter and antenna in a single structure that possesses both radiation and filtering functions. As a result, the losses, and interference between the antenna and the bandpass filter is tackled. However, the proposed filtennas were of a fixed band of operation and lacked the flexibility to accommodate new services. Reconfigurable filtennas which are able to switch their characteristics according to the requirements are widely adopted in modern RF system applications. Nevertheless, these reconfigurable filtering antennas are not capable of efficiently switching between transmit (Tx) and receive (Rx) channels which restricts their use in Time Division Duplex (TDD) RF front-end systems. Therefore, in this research project, a two-port antenna with the integrated filtering and transmit (Tx) – receive (Rx) switching functions for Time Division Duplex (TDD) transmission is proposed. RF signals are fed to a square radiating patch through two orthogonal ports to excite Tx and Rx modes. The filtering function is implemented by incorporating two symmetric square ring resonators working as–bandpass filter into both feeding line paths to increase the selectivity of each channel and improve the isolation between the two ports. Frequency reconfiguration between the two ports is realised by etching a rectangular slot in the feeding point for each path and placing a PIN diode in suitable places. The measurement results agree well with the simulated values, with a return loss better than -15 dB showing the maximum broadside realised gain of 2.4 dB at a centre frequency of 2.4 GHz, with an omnidirectional radiation pattern and port-to-port isolation of over 40 dB, which is sufficient to reduce channel interference. The benefits of the proposed switchable filter integrated antenna include satisfactory performance in terms of filtering, radiation, flat in-band gain response, out-of-band frequency suppression, and high port to port isolation when it is connected with either Tx or Rx port. Hence, the proposed filtering antennas with Tx/Rx mode reconfiguration are a good candidate for use in modern TDD RF front-end circuits that requires multifunctional operation devices.